Studi Kasus Pada Ruas Jalan Kecamatan Batu Ketulis Lampung Barat dengan Menggunakan Analisis Komputasi dan Metode Penanganannya - Nawawi, M Lucky Apriansyah; Iswan, I; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
Batu Ketulis is a sub-district located in West Lampung Regency, Lampung province. West Lampung is one of the areas in Lampung that has landslide-prone potential. This study is to determine the value of slope safety factors and calculate the stability of slopes using Bronjong to hold the soil carrying capacity to be safe and not landslide, which is calculated using computational programs with fellenius method, bishop with saturated, partially saturated, and unsaturated groundwater face conditions. The results showed that soil parameters affect the stability of the slope, the condition of fully saturated soil has the lowest value compared to other conditions. From the results of the study obtained the value of the smallest safe factor before handling, namely at location II with an elevation of 20 m and a slope angle of 30° ,35° ,40° of 1,074, 1,023, 1,008 in the condition of fully saturated groundwater face. In the condition of the slope after handling using bronjong obtained a value of 2,462, 2,303, 2,223 for the Fellenius method, while for the Bishop method of 2.12, 2,006, 1.95. Handling using bronjong has a big effect on increasing safe factors so that landslide handling using bronjong is quite stable if applied at the research site.